Dengue dynamics: modeling spread and environmental interactions - Matto, Joaquín (2024)
The objective of this study is to analyze the behavior of dengue fever in the city of La Plata during one year, considering temperature as an environmental factor, its influence on the mosquito population and the transmission of the DENY virus (which causes dengue fever, also known as dengue fever). To become aware of the magnitude of the problem in the future, and using the temperature estimated by the global warming trend, we sought to project an increase in average annual temperatures for the coming years, and thus estimate the impact on the spread of dengue fever. The Netlogo simulation tool was used to model the behavior of a mosquito population and the spread of the dengue virus through contact with the human population. Using official data from the National Meteorological Service, a scenario of spread was simulated for the period November 2022- November 2023, and the increase in temperature due to climate change was projected to simulate how it affects the spread of the virus and the mosquito population, maintaining the same trend for 2024, 2025 and 2030. It was concluded that climate change may generate an expansion in both the size of mosquito populations and their annual activity, leading to the appearance of dengue outbreaks outside the identified warmer seasons.